Investigations of Shock Tunnel Dynamics and Energy Realization (a197a97d-a574-4dd6-b892-bc2dba4e791b) - Joshua Hoffman; Braden Lusk; Kyle Perry (International Society of Explosives Engineers, 2009)
This study explores how different geometries affect the shock tunnel’s performance and is broken down into three phases. Phase 1: Open arena testing in which theoretical energies produced by the detonation of small (<1.0 kg) charges are compared to actual experimental values. Phase 2: Shock Tunnel testing in which realized energies are experimentally recorded for the UK and S&T shock tunnels. Phase 3: Analysis of the data to begin building a pressure-forecasting tool for the UK shock tunnel given the explosive characteristics, sample size and desired pressure and impulse.